Surface treatment method for member having base material and glaze layer
By using a slurry of inorganic oxide particles and a hydrolyzed organic group coating, the surface treatment method addresses durability issues in glazed materials, ensuring long-lasting antifouling performance despite exposure to harsh chemicals.
Patent Information
- Application Number
- JP2023116059
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-24
AI Technical Summary
Existing surface treatment methods for glazed materials, such as hygiene pottery, fail to provide sufficient durability against frequent exposure to strong acids and bases, leading to early loss of antifouling function due to insufficient hydroxyl group formation and surface roughness issues.
A surface treatment method involving a slurry of inorganic oxide particles dispersed in a pH-adjusted alkaline solution is applied to create more hydroxyl groups on the surface, followed by a coating agent with hydrolyzed organic groups to enhance binding, thereby improving durability.
The method enhances the durability of the coating on glazed surfaces, maintaining antifouling properties even in high-load environments with frequent exposure to strong detergents and bases.
Smart Images

Figure 2025012889000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface treatment method for applying a highly durable coating to the surface of a member having a glaze layer, such as sanitary ware. [Background technology]
[0002] Sanitary ware is used in environments where tap water, filth, and soap are present. When tap water adheres to the surface of the sanitary ware, the silica and calcium contained in the tap water form limescale as it dries. In addition, metal soap stains and filth formed when soap reacts with calcium and magnesium in the tap water tend to adhere to the sanitary ware surface. To improve the resistance to adhesion and removability of such stains, a technology is known for applying a coating to the sanitary ware surface to modify it.
[0003] For example, Japanese Patent Laid-Open Publication No. 11-21186 (Patent Document 1) describes a method of increasing the hydroxyl groups by spraying water or water vapor as a pretreatment for coating the sanitary ware surface, in order to form a water-repellent film with excellent durability on the glaze layer of the sanitary ware (paragraphs 0010 to 0011).
[0004] In addition, the following method has been disclosed as a pretreatment for coating glass, which has a similar chemical composition to sanitary ware.
[0005] JP 2002-517372 A (Patent Document 2) describes that in order to improve the durability of a water-repellent film on a glass substrate, a dispersant containing an abrasive selected from the group consisting of alumina, ceria, iron oxide, garnet, zirconia, silica, silicon carbide, chromium, pumice, and diamond, and an acid solution selected from the group consisting of hydrochloric acid, sulfuric acid, tartaric acid, phosphoric acid, hydrobromic acid, nitric acid, acetic acid, trifluoroacetic acid, oxalic acid, and citric acid is applied to the glass substrate, and then a water-repellent film is formed, thereby improving the abrasion resistance (paragraph 0011).
[0006] Japanese Patent Laid-Open Publication No. 9-2840 (Patent Document 3) describes a method of removing steep steps on a glass substrate by ceria polishing, and then coating the substrate with a fluorocarbon chemically adsorbed film (paragraphs 0011 to 0015).
[0007] Japanese Patent Laid-Open Publication No. 11-50006 (Patent Document 4) describes that in order to remove oily stains, stains caused by sparingly soluble calcium salts, and permanent stains mainly composed of silica gel, the surface of a glass substrate is cleaned with a cleaning agent containing an abrasive (single oxides such as silica, alumina, zirconia, ceria, yttria, boronia, magnesia, calcia, ferrite, amorphous titania, and hafnia, as well as barium titanate, calcium silicate, water glass, aluminosilicates, calcium phosphate, and the like) and at least one selected from the group consisting of surfactants, acids, bases, and solvents, followed by coating (paragraphs 0014 to 0015 and 0032).
[0008] The republished publication WO2014 / 084380 (Patent Document 5) describes a method of polishing the surface of a glass article using a polishing liquid in which an abrasive such as ceria or zirconia is dispersed in a liquid having a pH of 3 to 9.8 in order to prevent fading or clouding of the glass article and the appearance of latent scratches (paragraphs 0007, 0028, 0043, and 0064). [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Japanese Patent Application Publication No. 11-21186 [Patent Document 2] Special Publication No. 2002-517372 [Patent Document 3] Japanese Patent Application Publication No. 9-2840 [Patent Document 4] Japanese Patent Application Publication No. 11-50006 [Patent Document 5] WO2014 / 084380 publication Summary of the Invention [Problem to be solved by the invention]
[0010] In components with a glaze layer, such as sanitary ware, the glass that constitutes the glaze layer is a chemically stable substance, so even if water or water vapor is sprayed onto it, the generation of hydroxyl groups is insufficient. In addition, there are not many alkali metal components that can be removed even with the use of acid, and the acid promotes dehydration condensation of adjacent hydroxyl groups on the surface of the glaze layer. Therefore, in the methods described in Patent Documents 1 and 2, the generation of hydroxyl groups that serve as bonding points with the coating agent is insufficient, resulting in low durability of the coating.
[0011] As described in Patent Documents 3 to 5, polishing a glass substrate with a polishing solution containing dispersed inorganic particles to smooth the surface is widely practiced. However, the glaze layer contains many hard crystal particles such as zircon added for color development and gas generated during firing of the base material as bubbles, and polishing with particles exposes the crystal particles and bubbles inside the glaze layer, which results in a rougher surface and a lower gloss.
[0012] It is desired that the coating on the surface of sanitary ware maintains its functions such as antifouling properties for a long period of time, such as several years, even in a high-stress environment where the sanitary ware is frequently cleaned with strong acid or strong alkali chemicals. The present inventors have revealed that when a coating containing a surface modifier is applied to sanitary ware that has been subjected to the pretreatments described in Patent Documents 1 to 5, the functions provided by the surface modifier are lost early in the high-stress environment to which the sanitary ware is exposed, and the coating does not have sufficient durability.
[0013] The inventors have discovered a pretreatment method for coating that has good durability even under high load environments, and have arrived at the present invention. That is, the present invention aims to provide a surface treatment method that achieves high durability by increasing the number of bonding points with the coating agent without changing the surface properties such as the gloss and surface roughness of the surface of a member having a glaze layer. [Means for solving the problem]
[0014] The surface treatment method according to the present invention is a method for treating a surface of a member comprising a base material and a glaze layer, the method comprising dropping a slurry having a pH of 9 to 14 inclusive in which inorganic oxide particles are dispersed, sliding the slurry using a slider, and then applying a coating agent to the surface of the member, the method comprising the steps of: The coating agent comprises a hydrolyzable silicon compound having an organic group bonded to a silicon atom. Effect of the Invention
[0015] According to the present invention, the durability of the coating on the surface of a component can be improved by using a slurry of inorganic oxide particles adjusted to a specific pH for pretreatment of the coating, and thus the coating on the surface of the component can be prevented from losing its function even when used under a high-load environment. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a graph showing the results of the zeta potential of inorganic oxide particles versus changes in pH of the slurry in Test 1. [Diagram 2] FIG. 1 shows the results of the change in water contact angle over time in an immersion test in an aqueous sodium hydroxide solution in Test 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Materials In the present invention, the member comprises a base material and a glaze layer on the base material, and is preferably sanitary ware or an enamel product, more preferably sanitary ware. In sanitary ware, the base material is the base material of the sanitary ware. In enamel products, the base material is cast iron or a steel plate. In the present invention, sanitary ware means a ceramic product used in bathrooms, toilet spaces, dressing rooms, washrooms, kitchens, etc. Specifically, it means a toilet bowl, a urinal, a toilet bowl stool, a toilet tank, a washbasin, a hand washing basin, etc.
[0018] Base for sanitary ware In the present invention, the sanitary ware body is not particularly limited, and any known sanitary ware body used for sanitary ware can be used. The sanitary ware body may be any conventionally known sanitary ware body obtained by preparing, molding, and firing silica sand, feldspar, limestone, clay, or the like as raw materials.
[0019] In one embodiment of the present invention, an intermediate layer made of another base material having properties different from those of the sanitary ware base material may be provided between the glaze layer and the sanitary ware base material, which makes it possible to suppress air bubbles from penetrating from the sanitary ware base material into the glaze layer during the firing process during production, and forms a glaze layer that is excellent not only in appearance but also in cleanability.
[0020] Glaze layer In the present invention, the arithmetic mean linear roughness Ra of the surface of the glaze layer is 0.03 μm or more and 2.5 μm or less. Preferably, the arithmetic mean linear roughness Ra of the surface of the glaze layer is 0.03 μm or more and 1.5 μm or less. More preferably, the arithmetic mean linear roughness Ra of the surface of the glaze layer is 0.03 μm or more and 1.0 μm or less.
[0021] Here, the arithmetic mean linear roughness Ra is obtained in accordance with JIS B0633 (2001) "7. Methods and procedures for evaluation using a stylus surface roughness tester" using a stylus surface roughness tester conforming to JIS B0651 (2001). In the present invention, the arithmetic mean linear roughness Ra of the surface of the glaze layer is considered to be the same as the arithmetic mean linear roughness Ra of the surface of the sanitary ware. Therefore, it is possible to obtain the arithmetic mean linear roughness Ra of the glaze layer by measuring the arithmetic mean linear roughness Ra of the surface of the sanitary ware. According to one embodiment of the present invention, the glaze layer has a composition calculated in terms of oxides and shown in Table 1 below.
[0022] [Table 1]
[0023] According to another embodiment of the present invention, the glaze layer may contain Fe2O3, TiO2, BaO, B2O3, Li2O, Sb2O3, CuO, MnO, NiO, CoO, MoO3, SnO2, PbO, etc. in addition to the components listed in Table 1 above. The glaze layer may also contain particles. The particles include crystalline particles contained in the glaze raw materials and crystalline particles precipitated by firing. The material of the particles may be zircon, quartz, diopside, anorthite, etc.
[0024] In the present invention, the color of the glaze layer is not particularly limited as long as the composition of the glaze is within the range of Table 1. Examples of the color of the glaze layer include white, black, ivory, pink, gray, brown, beige, green, red, and blue.
[0025] In the present invention, the arithmetic mean linear roughness Ra (0.03 μm or more and 2.5 μm or less) of the surface of the glaze layer may be such that the surface of the glaze layer is processed so that Ra satisfies the above range, or the surface of the base material may be processed so that the Ra of the glaze layer thereon satisfies the above range.
[0026] Sanitary ware manufacturing In the present invention, the sanitary ware can be produced, for example, by first forming a glaze layer on a molded body obtained by molding raw materials for the sanitary ware, and then firing the molded body. Specifically, the sanitary ware can be produced by the following method.
[0027] First, a molded body that will be the base material for the sanitary ware is prepared. This is produced by casting a conventionally known sanitary ware slip prepared from raw materials such as silica sand, feldspar, limestone, clay, etc., into a mold made of plaster, etc. After drying, the molded body is glazed as described below.
[0028] The raw materials forming the glaze are preferably those capable of realizing the composition of the glaze layer described in Table 1 above. In addition, as the glaze raw materials, mixtures of natural mineral particles such as silica sand, feldspar, limestone, etc., pigments such as cobalt compounds and iron compounds, opacifiers such as zirconium silicate and tin oxide, etc. may be used. In one embodiment of the present invention, the composition of the glaze raw materials may be, for example, 10wt% to 30wt% feldspar, 15wt% to 40wt% silica sand, 10wt% to 25wt% calcium carbonate, 10wt% or less each of corundum, talc, dolomite, and zinc oxide, and 15wt% or less in total of opacifiers and pigments. The glaze can be obtained, for example, by melting the glaze raw materials as described above at a high temperature and then quenching and vitrifying them.
[0029] The above-mentioned glaze is applied to the dried molded body, and then dried and fired to form a glaze layer on the base for sanitary ware. The firing temperature can be, for example, a temperature between 1000°C and 1300°C at which the glaze softens.
[0030] The surface of the formed glaze layer may be subjected to a surface treatment as necessary within a range in which Ra satisfies the above-mentioned range. For example, blasting or etching may be performed. In blasting, the material / shape / particle size of the media used, the processing time per unit area, whether the processing is dry or wet, and the like can be controlled to obtain a glaze layer surface with Ra that satisfies the above-mentioned range. In etching, the pattern of the photomask, the concentration / type / temperature of the etching solution, whether stirring is performed, and the like can be controlled to obtain a glaze layer surface with Ra that satisfies the above-mentioned range. This can improve the glossiness of the surface, or reduce the glossiness to give it a matte finish.
[0031] In the present invention, in addition to the above-mentioned methods for manufacturing the base material and glaze layer for sanitary ware, for example, methods for manufacturing the base material and glaze layer for sanitary ware described in JP 2021-134133 A, JP 2020-147492 A, WO99 / 61392 A, etc. can be used. In this specification, by referring to the above publications, the methods for manufacturing the base material and glaze layer for sanitary ware described in these publications are incorporated into the description of this specification as methods for manufacturing the base material and glaze layer for sanitary ware that can be used in the present invention.
[0032] In the present invention, a step of removing dirt present on the surface of the glaze layer may be added before the step of pre-treatment of the coating. In the step of removing dirt, known means such as ultrasonic cleaning, blowing with a cleaning tool such as sponge / cloth / cotton, ultraviolet treatment, ozone treatment, plasma treatment, and flame treatment may be used. For ultrasonic cleaning or blowing with a cleaning tool, water, acid, alkali, surfactant, or organic solvent may be used.
[0033] Coating pretreatment As a pretreatment for coating, a slurry consisting of inorganic oxide particles and an alkaline aqueous solution, which will be described later, is applied to the surface of the member to be coated. Specifically, the slurry is dropped onto the surface to be coated, and the sanitary ware surface is rubbed with a slider such as a sponge, buff, or cloth. After the rubbing, it is preferable to remove the slurry to obtain a clean ware surface. For example, the slurry may be rinsed with purified water such as ultrapure water or ion-exchanged water, and the water may be dried by air blowing or the like.
[0034] The charge on the surface of inorganic oxide particles changes depending on the pH of the slurry solution. This change in the surface charge of the particles can be measured by the "Method of Measuring Zeta Potential" described later. In general, the surface charge of inorganic oxide particles takes a negative value in an alkaline aqueous solution. When the surface charge takes a negative value, it is considered that a large number of hydroxyl groups are present on the surface of the inorganic oxide. In the coating pretreatment process, it is considered that the hydroxyl groups on the surface of the inorganic oxide particles act on the sanitary ware surface, and more hydroxyl groups can be created on the surface of the sanitary ware compared to after pretreatment by the conventional technology. The alkoxysilyl group or chlorosilyl group of the coating agent described later reacts with moisture in the air and the hydroxyl groups on the surface of the sanitary ware to obtain a strong bond. In other words, compared to pretreatment by the conventional technology, the number of bonds of the coating agent with the glaze layer increases, or the bond density of the coating agent on the glaze layer increases, and the sanitary ware according to the present invention can have a coating on the surface of the sanitary ware that has high durability against strong acid or strong base detergents.
[0035] Inorganic Oxide Particles Inorganic oxide particles that can be used in the present invention include cerium oxide, aluminum oxide, zirconium oxide, silica, titanium oxide, iron oxide, etc. In the present invention, it is preferable to use cerium oxide because it has a low Mohs hardness and is therefore less likely to damage the surface of the glaze layer.
[0036] Preparation of slurry A slurry can be obtained by adding an alkaline aqueous solution with an adjusted pH to inorganic oxide particles and stirring them. A stirrer or magnetic stirrer can be used for stirring.
[0037] Slurry Concentration From the viewpoints of processing speed and ease of handling, the concentration of the slurry is preferably from 1 to 50% by weight, and more preferably from 1 to 30% by weight.
[0038] Slurry pH Examples of the alkaline component include sodium hydroxide, potassium hydroxide, sodium carbonate, sodium hydrogen carbonate, sodium silicate, sodium phosphate, ammonia, etc., and may be a mixture of these components. In the present invention, the pH of the slurry is 9 to 14, preferably 10 to 14, and more preferably 11 to 14.
[0039] Average particle size of inorganic oxide particles The average particle size of the inorganic oxide particles contained in the slurry is preferably about 0.01 to 100 μm, and more preferably about 0.01 to 30 μm, from the viewpoints of preventing damage to the surface of the glaze layer and preventing crystals and bubbles contained inside the glaze layer of the sanitary ware from appearing on the outermost surface.
[0040] The average particle size of the inorganic oxide particles can be measured using a laser diffraction particle size distribution analyzer (e.g., Partica LA960 manufactured by HORIBA, Mastersizer 3000 manufactured by Malvern, Microtrac MT-3000 manufactured by Nikkiso Co., Ltd.), and can be expressed as the median size (D50).
[0041] The average particle size of inorganic oxide particles is measured by measuring the median diameter (D50) under the following measurement conditions in accordance with the particle size analysis - laser diffraction and scattering method specified in JIS Z8825 (2013). [Particle size measurement conditions] Dispersion liquid: ultrapure water Dispersant: None Warm-up time: 10 minutes or more Sample concentration Transmittance (semiconductor laser): 80-90% Transmittance (LED):70-90% Ultrasonic exposure time: 1 minute Circulation speed: 10 Stirring speed: 10 Refractive index (cerium oxide): 2.20 Refractive index (aluminum oxide): 1.66 Refractive index (water): 1.33 Software: LA-960 for Windows P2001246G 8.00
[0042] How to measure zeta potential According to the optical measurement method of colloidal dispersion system-zeta potential specified in JIS Z8836 (2017), the zeta potential is measured by electrophoretic laser Doppler method using the zeta potential measurement system ZETASIZER NANO-ZS (Malvernpanalytical). Under the following conditions, an acidic / alkaline aqueous solution or a slurry consisting of ultrapure water and inorganic oxide particles is dispersed for a specified time using an ultrasonic device. The pH of the slurry is measured by the method described in the pH measurement method below, and the slurry is injected into a capillary cell and the zeta potential is measured, so that the zeta potential of the inorganic oxide particles at a specific pH can be obtained. The zeta potential is preferably -10mV or less, more preferably -30mV or less, from the viewpoint that the hydroxyl groups on the inorganic oxide surface act to create hydroxyl groups on the surface of the glaze layer, and the amount of hydroxyl groups on the glaze surface affects the durability of the coating. [Zeta potential measurement conditions] Acidic aqueous solution: Hydrochloric acid Alkaline solution: Sodium hydroxide solution Slurry concentration: 0.05% by weight Ultrasonic device: Desktop ultrasonic cleaner Sonocleaner (manufactured by Kaijo) Ultrasonic exposure time: 2 minutes Zeta potential measurement temperature: 25℃ Slurry stabilization time: None
[0043] How to Measure pH The pH is measured at 25°C using a pH meter (LAQUAtwin, manufactured by HORIBA) in accordance with the pH measurement method of JIS Z8802 (2011).
[0044] Sliding The sliding is performed by dropping a slurry onto the surface of the glaze layer and moving the slider on the surface of the glaze layer in the presence of the slurry, preferably by reciprocating or circularly moving the slider while applying a predetermined pressure. In order not to change the surface properties of the member before and after the sliding, the change in glossiness before and after the sliding is preferably 5 or less, more preferably 3 or less. The sliding conditions are preferably the following sliding condition 1, more preferably the following sliding condition 2, and even more preferably the following sliding condition 3, from the viewpoint of the processing speed and the change in glossiness of the surface of the glaze layer. In order to prevent excessive absorption of the slurry into the slider, the slider may be impregnated in advance with the alkaline aqueous solution used in the preparation of the slurry, as necessary, within the range not deviating from the preferred concentration range of the slurry. In addition, in order to prevent excessive use of the slurry, it is preferable to process the slider to a size appropriate for the size of the member before use. It is more preferable that the contact area of the slider is equal to or smaller than the area of the surface of the member to be coated, and that the length in the height direction of the slider is equal to or smaller than the length in the width or depth direction of the slider when the slider is a rectangular prism, and is equal to or smaller than the radius of the slider when the slider is a cylinder.
[0045] Sliding conditions <Sliding condition 1> Slurry concentration: 0.1~50wt% Slurry amount: Amount that permeates the entire slider and does not drip from the slider when there is no load on the slider. Sliding pressure: 10~1000g / cm 2 Slider: Sponge, buff, cloth Sliding speed: 1-70cm / sec Accumulative sliding time: 0.01 to 30 seconds / cm 2 <Sliding condition 2> Slurry concentration: 0.1 to 30 wt% Slurry amount: Amount that permeates the entire slider and does not drip from the slider when no load is applied. Sliding pressure: 100~500g / cm 2 Slider: Sponge Sliding speed: 1-30cm / sec Accumulative sliding time: 0.1 to 30 seconds / cm 2 <Sliding condition 3> Slurry concentration: 0.1 to 20 wt% Slurry amount: 0.1 to 1 g / cm 2 The amount of the solvent should be within the range of 100% so that it can fully permeate the entire surface of the slider and will not drip off when there is no load on the slider. Sliding pressure: 100~500g / cm 2 Slider: Urethane sponge Sliding speed: 3-10cm / sec Accumulative sliding time: 1-30 seconds / cm 2
[0046] coating A coating agent, which will be described later, is applied to the surface of the member after the pretreatment. A known method can be used for applying the coating agent. For example, the coating agent can be applied by dipping, spin coating, wiping, vacuum deposition, spray gun, or the like. After the coating agent is applied to the surface of the glaze layer, it is dried and cured as necessary, and then, in some cases, preferably, the surface of the sanitary ware is washed with a neutral detergent and a sponge, and then thoroughly rinsed with ultrapure water to obtain a sanitary ware containing the coating agent on the surface of the glaze layer. The coating is preferably a thin film so as not to change the texture of the sanitary ware. The coating thickness is preferably 100 nm or less, more preferably 30 nm or less, and even more preferably 10 nm or less.
[0047] Coating Agent The coating agent comprises a hydrolyzable silicon compound in which an organic group is bonded to a silicon atom. The silicon compound contains an alkoxysilyl group or a chlorosilyl group. Preferably, the organic group is hydrophobic, and specifically, comprises at least one selected from the group consisting of an alkyl group, a fluoroalkyl chain, a perfluoroalkyl chain, a perfluoropolyether chain, and a silicone chain.
[0048] In one embodiment of the silicon compound preferably used in the present invention, the alkyl group is a straight chain having 5 to 30 carbon atoms, and the alkoxysilyl group or chlorosilyl group is present at one end.
[0049] According to another embodiment of the silicon compound preferably used in the present invention, the organic group has a straight or side chain of perfluoropolyether, has any one of CFO, CFCFO, and CFCFCFO, has a molecular weight of 500 to 10,000, and has an alkoxysilyl group or a chlorosilyl group at one or both ends.
[0050] According to another embodiment of the silicon compound preferably used in the present invention, the organic group has a silicone chain, the silicone chain being dimethylsilicone, methylphenylsilicone, or methylhydrogensilicone, and the alkoxysilyl group or chlorosilyl group is present at one end, both ends, or as part of the side chain.
[0051] In the present invention, the silicon compound more preferably used is composed of the following components and has a compound containing a perfluoropolyether chain represented by formula (a) as an active ingredient.
[0052] [ka] (wherein l:m:n=23.2:22.3:0.4 (average value), and X Simeans an organic group containing an average of 3.0 Si atoms, with no fluorine atoms in the Si atoms, bound to a hydroxyl group or a hydrolyzable group. The hydrolyzable group means an alkoxy group or a halogeno group. Specifically, it is -OCH3, -OCH2CH3, or -Cl. The repeating units in the formula are arranged randomly.
[0053] The coating agent preferably comprises the silicon compound and a solvent. The solvent can be any solvent that can dissolve or disperse the silicon compound, and can be at least one selected from organic solvents such as alcohol and ether, and water. When the silicon compound is a compound that contains a perfluoropolyether chain, an organic compound that contains a fluoroalkyl group can be used as the solvent.
[0054] Coating application The coating agent can be applied to the surface of the glaze layer by, for example, dipping, spin coating, wiping, vacuum deposition, spray gun, etc. Regardless of the application method of the coating agent, it is preferable to apply the coating under conditions that the coating thickness on the surface of the glaze layer is 100 nm or less, and more preferably 10 nm or less.
[0055] According to one embodiment of the application of the coating agent preferably used in the present invention, a spray gun can be used as a means for applying the coating agent, and it is preferable that the spray pressure is 0.01 to 0.5 MPa, the spray distance is 10 to 30 cm, and the spray movement speed is 0.1 to 10 cm / sec.
[0056] According to one embodiment of the application of the coating agent preferably used in the present invention, wiping can be used as a means for applying the coating agent, and in wiping, the coating agent can be applied to the surface of the glaze layer using a cloth, sponge, cotton, etc. Wiping is preferably performed with a sliding pressure, number of sliding strokes, and amount of coating agent used that can uniformly coat the surface of the glaze layer and that does not remove the applied coating.
[0057] Surface properties of components to which coating agents are applied By the above "application of coating agent", a coating with excellent durability can be obtained on the surface of the glaze layer. When the above "coating agent" has a hydrophobic function, a coating with particularly excellent alkali resistance can be obtained. When a coating is obtained on the surface of the glaze layer by the above "application of coating agent" using a coating agent containing a compound containing a perfluoropolyether chain represented by formula (a) described in the above "coating agent" as an active ingredient, the water contact angle of the surface of the glaze layer having the coating after a test in which the glaze layer is immersed in a 1.5 wt % sodium hydroxide aqueous solution maintained at 40°C for 14 hours is changed by 20% or less from the water contact angle before the test. EXAMPLES
[0058] The present invention will be described in more detail with reference to the following examples, although the present invention is not limited to these examples.
[0059] How to Measure pH The pH was measured at 25°C using a pH meter (LAQUAtwin, manufactured by HORIBA) in accordance with the pH measurement method of JIS Z8802 (2011).
[0060] Measurement method using a stylus-type surface roughness gauge The arithmetic mean roughness Ra was measured in accordance with JIS B0633 (2001) "7. Evaluation method and procedure using a stylus surface roughness tester" using a stylus surface roughness tester conforming to JIS B0651 (2001), specifically, a SURFTEST SV-3200 (manufactured by Mitutoyo).
[0061] How to measure zeta potential The zeta potential was measured by electrophoretic laser Doppler method using the ZETASIZER NANO-ZS (Malvernpanalytical) zeta potential measurement system according to the optical measurement method of colloidal dispersion zeta potential specified in JIS Z8836 (2017). Under the following conditions, an acidic / alkaline aqueous solution or a slurry consisting of ultrapure water and inorganic oxide particles was dispersed for a specified time using an ultrasonic device. The pH of the slurry was measured by the method described in the pH measurement method above, and the slurry was injected into a capillary cell and the zeta potential was measured to determine the zeta potential of inorganic oxide particles at a specific pH. <Zeta potential measurement conditions> Acidic aqueous solution: Hydrochloric acid Alkaline solution: Sodium hydroxide solution Slurry concentration: 0.05% by weight Ultrasonic device: Desktop ultrasonic cleaner Sonocleaner (manufactured by Kaijo) Ultrasonic exposure time: 2 minutes Zeta potential measurement temperature: 25℃ Slurry stabilization time: None
[0062] How to measure water contact angles The static contact angle of water with respect to the surface of the surface layer was measured under the following measurement conditions using the following device and software. Equipment: DMs-301 (manufactured by Kyowa Interface Science Co., Ltd.) Software: FAMAS integrated interface measurement / analysis system Version:5.0.16 Measurement method: Droplet method Droplet volume: 2.0μL Waiting time: 1000ms Analysis method: θ / 2 method Temperature: 25℃
[0063] How to measure gloss According to the specular gloss measurement method stipulated in JIS Z8741 (1997), a gloss meter (NOVO GLOSS FLEX60, manufactured by RHOPOINT) was used to measure the 60° gloss of the glaze layer surface before pretreatment for coating and the glaze layer surface after coating was applied. The gloss was measured at five points and the average value was calculated. The thickness of the coating used in the following Test 1 and Test 2 was approximately 2 nm, and since there is no effect on the gloss before and after coating, the gloss of the glaze layer surface after coating is equivalent to the gloss of the glaze layer surface after pretreatment for coating.
[0064] [Test 1] Sanitary ware manufacturing <Preparation of base material for sanitary ware> A sanitary ware slip prepared from raw materials such as silica sand, feldspar, limestone, and clay was cast into a plaster mold to obtain a molded body. This molded body was then dried. The dried molded body was then fired in the firing process described below to produce the "sanitary ware base material."
[0065] <Preparation of glaze> A number of glaze raw materials were prepared, each having the composition calculated as oxide, as shown in Table 1. 600 g of each glaze raw material, 400 g of water, and 1 kg of alumina balls were placed in a 2-liter ceramic pot and ground in a ball mill for approximately 65 hours to obtain a glaze.
[0066] Glaze was spray-coated onto the dried molded body, and fired at 1100-1200°C to produce a base for sanitary ware with a glaze layer. The arithmetic mean roughness Ra was measured using a stylus surface roughness measuring instrument conforming to JIS B0651(2001) in accordance with "7. Methods and procedures for evaluation using a stylus surface roughness measuring instrument" of JIS B0633(2001).
[0067] Before carrying out the pretreatment for coating, the surface of the glaze layer was washed with a commercially available sponge soaked in a neutral detergent to remove dirt from the surface of the glaze layer. After washing, the glaze layer was rinsed with ultrapure water and the moisture was removed with an air duster.
[0068] Coating pretreatment <Preparation of aqueous solution> Sodium hydroxide was used to prepare alkaline aqueous solutions having a pH of about 12 and about 9. As a control, an acidic aqueous solution containing 4.3% by weight of hydrochloric acid and having a pH of about 0 was prepared with reference to the examples in Patent Document 2 (paragraph 0041).
[0069] <Preparation of slurry> Slurries were prepared by dispersing cerium oxide A in the aqueous solutions of each pH prepared above so that the content of cerium oxide A was 15% by weight. Cerium oxide A was dispersed in an alkaline aqueous solution of about pH 12 to obtain a slurry A of pH 12.4, in an alkaline aqueous solution of about pH 9 to obtain a slurry B of pH 9.4, in ultrapure water to obtain a slurry C of pH 7, and in an acidic aqueous solution of about pH 0 to obtain a slurry D of pH 0.3. Similarly, slurries were prepared by dispersing aluminum oxide in the aqueous solutions of each pH prepared above so that the content of aluminum oxide was 15% by weight. Aluminum oxide was dispersed in an alkaline aqueous solution of about pH 12 to obtain a slurry E of pH 12.4, in ultrapure water to obtain a slurry F of pH 6.8, and in an acidic aqueous solution of about pH 0 to obtain a slurry G of pH 0.3.
[0070] The pH of the slurry of inorganic oxide particles dispersed in the acidic / alkaline aqueous solution was measured by the above-mentioned "pH measurement method." The results are shown in Table 2.
[0071] The particle size of the inorganic oxide particles contained in the prepared slurry was measured by the above-mentioned "Method of Measuring Particle Size." The results are shown in Table 2.
[0072] The zeta potential of the inorganic oxide particles contained in the prepared slurry was measured using the above-mentioned "Method for measuring zeta potential." Measurements were performed three times per sample, and the average value and standard deviation of the three measurements are shown in Table 3 and Figure 1.
[0073] <Sliding using slurry and slider> Under the test conditions below, slurries A to G were dropped onto the surface of the glaze layer of the sanitary ware and scrubbed with a sponge. After that, the slurry remaining on the sanitary ware was removed using a clean sponge and water, and then the sanitary ware was rinsed with ultrapure water and then the water was blown off with an air duster to obtain sanitary ware A to G with clean surfaces. <Sliding conditions> Part size (width x depth x thickness): 4cm x 2cm x 1cm Slurry concentration: 15% by weight Slurry amount: 5g Sliding pressure: 300g / cm 2 Slider: Urethane sponge (Scotch-Brite Bath Shine, product number: BM12K) Slider size (width x depth x thickness): 2cm x 2cm x 2cm Number of strokes: 20 times Sliding speed: 4cm / sec Accumulative sliding time: 20 seconds / cm 2 Sliding stroke: 4cm
[0074] Preparation of coating agent 206 μl of the following agent was added dropwise to 30 g of a fluorine solvent (product name: NOVEC7200, manufactured by 3M) and stirred gently to obtain coating agent A with an active ingredient concentration of approximately 0.2% by weight. <Drugs> A reagent comprising the following components and containing as an active ingredient a compound containing a perfluoropolyether chain represented by formula (a):
[0075] [ka] (wherein l:m:n=23.2:22.3:0.4 (average value), and X Simeans that the compound contains an average of 3.0 Si atoms, and that the Si atom is bonded to an organic group that does not contain a fluorine atom and a hydroxyl group or a hydrolyzable group. The hydrolyzable group means an alkoxy group or a halogeno group. Specifically, it is -OCH3, -OCH2CH3, or -Cl. The repeating units in the formula are arranged randomly. These values were determined by liquid analysis of the reagent a using NMR. The number average molecular weight of the perfluoropolyether chain is, 19 From the F-NMR results, Si The existence of 1 H-NMR and 29 This was confirmed by the Si-NMR detection spectrum.)
[0076] (component) Fluoroalkyl ether (CAS No. 163702-06-4) 30-40% Fluoroalkyl ether (CAS No. 163702-06-5) 40-50% 10-20% of a compound containing a perfluoropolyether chain of formula (a) (active ingredient)
[0077] Coating application Coating agent A was applied under the following application conditions to the surface of the glaze layer of the sanitary ware that had been pretreated for coating, and then heated and dried for 180 minutes in a drying oven at 120°C. After that, it was naturally cooled to room temperature, and the surface was washed with a neutral detergent to obtain sanitary ware A to G that had been coated according to Examples 1 to 3 and Comparative Examples 1 to 4. <Coating conditions> Material size: 4cm x 2cm x 1cm Amount of coating agent used: 15g Application tool: Spray gun (product name: F110, manufactured by Meiji Machinery Co., Ltd.) Spray pressure: 0.04MPa Spray distance: 20cm Spray travel speed: 1cm / sec
[0078] The gloss of the glaze layer surface was measured at 5 points per sample before the pretreatment for coating and after application of the coating agent using the "gloss measurement method" described above. The average gloss and standard deviation of the glaze layer surface gloss, and the absolute value of the difference between the average gloss before and after sliding were taken as the gloss difference. The results are shown in Table 2.
[0079] Durability evaluation The coated sanitary ware A-G were immersed in a 1.5% by weight aqueous solution of sodium hydroxide maintained at 40°C. The coated sanitary ware A-G were removed at the specified time, exposed to running water, rinsed with ultrapure water, and the moisture was removed with an air duster. Next, the water contact angles of the coated sanitary ware A-G were measured at five points per sample using the method described in "Method for measuring water contact angles." The average values of the five-point measurements are shown in Table 2 and Figure 2.
[0080] When the water contact angle after immersion for 14 hours in a 1.5 wt % sodium hydroxide aqueous solution maintained at 40° C. was rated as “good”, when it was 100° or more, it was rated as “poor” when it was less than 100°. The results are shown in Table 2.
[0081] [Table 2]
[0082] [Table 3]
[0083] [Test 2] Sanitary ware was prepared in the same manner as in Test 1, and the surface of the glaze layer was washed with a commercially available sponge soaked in a neutral detergent to remove dirt from the surface of the glaze layer.
[0084] Coating pretreatment <Examples 4 to 8: Sliding using slurry and slider> Cerium oxide A with D50 = 0.8 μm and cerium oxide B with D50 = 27.4 μm were each dispersed in an alkaline aqueous solution to a concentration of 15% by weight to prepare slurries H and I with a pH of 12.6. Slurry H was dropped onto sanitary ware H to K, and slurry I was dropped onto sanitary ware L, and then scrubbed with a sponge.
[0085] The zeta potential of the inorganic oxide particles dispersed in the alkaline aqueous solution was measured by the above-mentioned "Method for measuring zeta potential".
[0086] <Comparative Example 5: Pretreatment with hot water> Warm water at 40°C was sprayed onto the sanitary ware M using a sprayer.
[0087] <Comparative Example 6: Pretreatment with alkaline aqueous solution> Sanitary ware N was immersed in an alkaline aqueous solution adjusted to pH 12.6 and subjected to ultrasonic waves for 5 minutes using a tabletop ultrasonic cleaner Sonocleaner (manufactured by Kaijo).
[0088] <Comparative Example 7: No pretreatment for coating> Sanitary ware O was not pretreated with coating.
[0089] Preparation of coating agent 206 μl of the agent described in Test 1 was added dropwise to 30 g of a fluorine solvent (product name: NOVEC7200, manufactured by 3M) and stirred gently to obtain coating agent A having an active ingredient concentration of approximately 0.2% by weight.
[0090] Coating application Coating agent A was applied to the surfaces of sanitary ware H to O that had been pretreated for coating under the application conditions described in Test 1, and the surfaces were heated and dried for 180 minutes in a drying oven at 120°C. After that, the surfaces were naturally cooled to room temperature, and the surfaces were washed with a neutral detergent to obtain sanitary ware H to O that had been coated according to Examples 4 to 8 and Comparative Examples 5 to 7.
[0091] The surface roughness of the glaze layer was measured at five points per sample before the coating pretreatment and after the application of the coating agent using the above-mentioned "measurement method with a stylus surface roughness meter." The average value and standard deviation of the surface roughness of the glaze layer surface are shown in Table 4.
[0092] The glossiness of the glaze layer surface was measured before the pretreatment of the coating and after the application of the coating agent using the "glossiness measurement method" described above. The average glossiness and standard deviation of the glaze layer surface, as well as the absolute value of the difference between the average glossiness before and after sliding, were calculated as the glossiness difference, and the results are shown in Table 4.
[0093] Durability evaluation The coated sanitary ware H to O were immersed in a 1.0 wt % sodium hydroxide aqueous solution maintained at 40°C. After a specified time, the coated sanitary ware H to O were removed and exposed to running water, then to ultrapure water, and the moisture was removed with an air duster. The water contact angles of the coated sanitary ware H to O were then measured using the method described in "Method for measuring water contact angles."
[0094] When the water contact angle after immersion for 16 hours in a 1.0 wt % aqueous sodium hydroxide solution maintained at 40° C. was rated as “good”, when it was 100° or more, it was rated as “poor”, when it was less than 100°. The results are shown in Table 4.
[0095] [Table 4]
[0096] [Test 3] The sliding conditions were as follows: sliding condition A and sliding condition B. The other conditions were the same as those in Example 5 of Test 2.
[0097] <Sliding condition A> Slurry concentration: 50wt% Slurry amount: Amount that permeates the entire slider and does not drip from the slider when there is no load on the slider. Sliding pressure: 1000g / cm 2 Slider: Sponge Sliding speed: 70cm / sec Accumulative sliding time: 30 seconds / cm 2
[0098] <Sliding condition B> Slurry concentration: 50wt% Slurry amount: Amount that permeates the entire slider and does not drip from the slider when there is no load on the slider. Sliding pressure: 1000g / cm 2 Slider: Sponge Sliding speed: 70cm / sec Accumulative sliding time: 60 seconds / cm 2
[0099] The glossiness of the surface of the glaze layer was measured before and after sliding using the "glossiness measurement method" described above. Under sliding condition A, the glossiness before sliding was 92, the glossiness after sliding was 88, and the glossiness difference was 4. Under sliding condition B, the glossiness before sliding was 92, the glossiness after sliding was 84, and the glossiness difference was 8.
[0100] A coating agent was applied to the sanitary ware that had been subjected to sliding conditions A and B in the same manner as in Example 5. Thereafter, durability was evaluated in the same manner as in Example 5. The results were "Good" for both sliding conditions A and B.
Claims
1. A method for treating the surface of a member comprising a base material and a glaze layer, the method comprising dropping a slurry having a pH of 9 to 14 inclusive, in which inorganic oxide particles are dispersed, sliding the slurry using a slider, and then applying a coating agent to the surface of the member, the method comprising the steps of: The surface treatment method, wherein the coating agent comprises a hydrolyzable silicon compound in which an organic group is bonded to a silicon atom.
2. 2. The surface treatment method according to claim 1, wherein the inorganic oxide particles have an average particle size of 0.01 to 100 μm.
3. 2. The surface treatment method according to claim 1, wherein the inorganic oxide particles are at least one selected from the group consisting of cerium oxide, aluminum oxide, silica, zirconium oxide, titanium oxide, and iron oxide.
4. The glaze layer is made of SiO 2 The surface treatment method according to claim 1, comprising:
5. The surface treatment method according to any one of claims 1 to 4, wherein a change in glossiness of the surface of the member before and after the sliding is 5 or less.
6. The surface treatment method according to claim 5 , wherein the amount of change is 3 or less.
7. The surface treatment method according to claim 1 , wherein the organic group comprises at least one selected from the group consisting of an alkyl group, a fluoroalkyl chain, a perfluoroalkyl chain, a perfluoropolyether chain, and a silicone chain.
8. The surface treatment method according to claim 1, wherein the inorganic oxide particles have a zeta potential of -10 mV or less when diluted with an aqueous sodium hydroxide solution to have the same pH as that of the slurry and dispersed in the aqueous solution at 0.05% by weight.
Citation Information
Patent Citations
Stain-resistant treatment product and its production
JP1997002840A
Water repellent treatment of ceramic article
JP1999021186A
Pretreatment of surface forming photocalytic hydrophilic coating film and cleaning agent and unedrcoating composition used therefor
JP1999050006A
Water-repellent surface treatment
JP2002517372A
Glass article
WO2014084380A1